BEST APPROXIMATION IN INTUITIONISTIC FUZZY n-NORMED LINEAR SPACES - Sen, M.; Debnath, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
The central issues that are addressed by the theory of best approximation are related to the questions of existence, uniqueness, characterizations and qualitative properties of the minimizing functions. The theory can also estimate the rapidity of convergence of a sequence of functions converging to a minimizing function. The aim of this article is to introduce and study the notions of best approximation, proximal set, Chebyshev set and approximatively compact set in the new setup of intuitionistic fuzzy n-normed linear spaces.